71‐1: Invited Paper: Additive Printing of Flexible Electronics. Issue 1 (May 2016) - Ng, Tse Nga; Mei, Ping; Ready, Steve; Whiting, Greg; Schwartz, David; Veres, Janos
Abstract : Digital, additive printing of electronic materials allows rapid, highly customizable fabrication, and low‐cost printed electronics are compelling for internet‐of‐things applications that require large volume of distributed devices, such as in sensor networks and smart packaging. The functionalities required of the embedded devices will vary over a broad spectrum from simple passive tags to powerful microprocessor controllers. In our prototype development, we apply two progressive printing approaches: simple systems are inkjet printed entirely from solution electronic inks, whereas more complex functions are met by printing interconnects between silicon ICs and printed passive components, to combine the advantages of flexible printed devices with the high performance of silicon chips.